Development of Microsoft Power Point Based Educational Game in Vocabulary Learning in Elementary School: Pengembangan Game Edukatif Berbasis Microsoft Power Point dalam Pembelajaran Kosa Kata di Sekolah Dasar - Chotimah, Chusnul; Hikmah, Khizanatul (Indonesian Journal of Education Methods Development, 2022)
This article aims to determine the development of Microsoft Power Point-based educational games in vocabulary learning at SD Muhammadiyah 2 Sidoarjo and to determine student responses to this educational game. The research approach used by researchers is development research because it makes a product that can help learning. The results showed that, 1) It is known how to develop this educational game, namely by finding problems in the field, collecting data, designing products, design validation, design revisions, product trials, limited trials, product revisions, and game distribution for all class students. 5. 2) From the experimental results of distributing games to 5 respondents, it is known that games are interesting and able to overcome the needs of learning Arabic vocabulary by obtaining 4.97 results on the Linkert Scale interval which means that they agree with Microsoft Power Point-based games. And when it was distributed to class 5, it was found that the respondent's results scored 4.94, which means that they strongly agree with the existence of educational games based on Microsoft Power Point. As for the results of the quizzioner distributed to grade 5 students, it is also known that the answers strongly agree with the existence of educational games based on Microsoft Power Point by 83%, agree 17%, and the answers disagree 0%. From these results, the researcher was able to draw the conclusion that educational games are a new tool for learning Arabic vocabulary for grade 5 at SD Muhammadiyah 2 Sidoarjo, have an attractive appearance, and are able to increase students' enthusiasm when learning Arabic vocabulary, and overcome the needs of students. Arabic vocabulary learning, and easy to use.